PEMANFAATAN RESIDU KILANG MINYAK PLAJU SEBAGAI PELARUT PADA PROSES PENCAIRAN BATUBARA (CO-PROCESSING) - Rasyid, Muhamad Hanif; Hidayat, Herman (Jurnal Energi dan Lingkungan (Enerlink), 2008)
This study presents the investigation on the reactivity of vacuum oil residue(VOR) as solvent in Banko coal liquefaction, so called ?Co-processing?. Processsolvent derived from BSU tests is used as reference solvent in this study. Theliquefaction tests are carried out using a gas-flow type autoclave (5L) with 200gcoal (daf), 400g of coal-derived solvent (b.p.300-420 oC), 1.0-3.0 wt% daf as Feof catalyst and elemental sulfur (S/Fe atomic ratio of 2.0) at 14.7MPa, 450oC for60min under a constant gas flow of H2-0.5%H2S. The study suggests that VORas solvent is much more reactive than process solvent under the same condition.Therefore the co-processing gives higher oil yield than coal liquefaction usingprocess solvent derived from BSU tests. It also produces lower CLB, CO+CO2and hydrocarbons yields. This indicates that there is a synergism effect betweenthe VOR as a donor solvent and the coal. The molecular structure of VOR at thefirst time was decomposed into molecular fragments. These fragments were thenattached onto the coal?s structure and lead to decompose the structure of thecoal. It was also found that co-processing consumed less hydrogen gas thanreference liquefaction process. In short, this finding obtained in this study cangive promising sight for implementing the coal liquefaction plant in Indonesia at acommercial scale.Kata kunci: vacuum oil residue, Banko, liquefaction, co-processing reactive,synergism effect